PAI Teachers' Strategies in Guiding the Practice of Islamic Teachings to Students at Madrasah Aliyah Zakiyun Najah, Sei Rampah District - Herbay Syahrial; Munawir Pasaribu; Mawaddah Nasution (International Journal on Integrated Education, 2026)
This study aims to describe and analyze the strategies used by Islamic Religious Education teachers in guiding the practice of Islamic teachings for students at Zakiyun Najah Islamic Senior High School, Sei Rampah District, while identifying the supporting and inhibiting factors and assessing their impact on the practice of Islamic teachings by students. The study used a qualitative approach with a case study design; data were collected through in-depth interviews, participatory observation, and documentation studies with the principal, vice principal of curriculum, subject teachers, and students, then analyzed using the Miles & Huberman interactive model and tested for validity through triangulation and member check. The research conceptual framework identified five guidance strategies applied by subject teachers, namely: (1) role model, as providing real examples through teacher behavior and mindset that reflect Islamic values; (2) habituation, through consistent instilling of routines of worship and morals; (3) giving advice, as conveying truth that is reflective and personal; (4) motivation, as a constructive approach that awakens students' internal drive to practice religious teachings; and (5) evaluation, as a continuous assessment of the consistency of students' practice of worship and morals for the purpose of improving subsequent strategies. These five strategies complement each other in an effort to bridge the gap between students' cognitive understanding and daily religious practices, and are relevant for strengthening the religious culture of the madrasah in a sustainable manner.